(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
AM4Life is a Competence Centre gathering more than 20 partners in academia, industry and the healthcare sector around Additive Manufacturing in the Life Sciences. We focus on six themes – Development of equipment and processes, AM for bioprocessing, AM for implants, Bioprinting, Printing for medication, and Implementation. In this talk I will highlight some key results from each theme, with a particular focus on my own theme, Additive Manufacturing of materials for implants, and in particular biodegradable such, for bone replacement. Biodegradable implants would not only provide the benefit of being replaced by the body’s own tissue, but would also provide a decreased risk for complications such as infection. Additive manufacturing of biodegradable materials not only allows for patient-specific and complex implant designs, but also for gradients of degradation rates, and a tailored local biological response. Cecilia Persson is a Professor in Applied Materials Science at Uppsala University (https://katalog.uu.se/profile/?id=N9-1332) and the President of the Scandinavian Society of Biomaterials. She currently directs research networks within the field of biomaterials and devices for the spine (MSCA ITN NU-SPINE and EIT Health SOFTBONE), as well as a Competence Centre for Additive Manufacturing in the Life Sciences (https://www.uu.se/en/research/am4life/).